Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) blends with poly(caprolactone) and poly(lactic acid): a comparative study - Tubio, Carmen R. (2023)
Poly(hydroxybutyrate-co-hidroxyvalerate) (PHBV) is a biodegradable polymer, which is a potential substitute for plastics made from fossil resources. Due to its practical interest in the field of tissue engineering, packaging, sensors, and electronic devices, the demand for PHBV with specific thermal, electrical, as well as mechanical requirements is growing. In order to improve these properties, we have developed PHBV blends with two thermoplastic biodegradable polyesters, including poly(caprolactone) (PCL) and poly(lactic acid) (PLA). We analysed the effect of these biopolymers on the morphological, wetting, structural, thermal, mechanical, and electrical characteristics of the materials. Further, the biodegradation of the samples in simulated body fluid conditions was evaluated, as well as the antibacterial activity. The results demonstrate that the blending with PCL and PLA leads to films with a dense morphology, increases the hydrophilic character, and induces a reinforcement of the mechanical characteristics with respect to pristine PHBV. In addition, a decrease in dielectric constant and a.c. electrical conductivity was noticed for PHBV/PLA and PHBV/PCL blends compared to neat PHBV polymer. All neat polymers and blends showed antibacterial properties against S. aureus, with more than 40% bacterial reduction, which increased to 72% in the presence of PCL polymer for a blend ratio of 50/50. Thus, it is demonstrated a suitable way to further tailor a variety of functionalities of PHBV for specific applications, by the development of polymer blends with PLA or PCL.